#BABIESOFINSTAGRAM: THE DIGITALLY MEDIATED LIVES OF ‘ASPIRING’ BABY MODELS AND BRAND REPS - Ruiz-Gomez, Alexandra; Gavilan, Diana; Avello, Maria (AoIR Selected Papers of Internet Research, 2020)
This paper is part of an on-going study of baby accounts created by ordinary parents to reach audiences outside friends and families. More specifically, the aim is to provide insights on the growing phenomenon of commercial forms of sharenting where parents seek money–making opportunities through the lives and images of children. A qualitative exploratory approach is used to shed light on the practices used by parents to try to garner the attention of brands on Instagram. Content analysis is carried out of 308 posts and the baby accounts behind these posts. Findings reveal that accounts in our sample are predominantly used to seek financial opportunities in the fashion industry. This is observed in the post images where brands are tagged and children appear in carefully staged poses that emphasize the baby’s looks and the clothes worn. The choice of hashtags added to the posts suggest a willingness to participate in baby model contests and brand representation searches. The commercial motivations of these accounts is also evident in the profile description, where parents indicate that the child is ‘an aspiring baby model’ or that the account is open to brand collaborations. This investigation extends emerging research on the growing presence of children on digital spaces when profit is involved. We discuss privacy issues surrounding the intensely mediated lives of children who are commodified to obtain rewards such as brand partnerships and free or discounted products or services.